2004
DOI: 10.1111/j.0141-9889.2004.00397.x
|View full text |Cite
|
Sign up to set email alerts
|

Accommodating health and social care needs: routine resource allocation in stroke rehabilitation

Abstract: This paper explores routine resource allocation processes in health and social care. While there has been a small body of work which has drawn on Lipsky's (1980) insights into street level bureaucracy, few have taken seriously the opportunity offered by ethnography to explore in detail the work of front-line staff as a way of observing policy processes in action. Utilising ethnographic data from research into the continuing care of adults who had suffered a first acute stroke, we analyse how staff accommodated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…[20][21][22] Over a 16-week period from January to May 2005, the authors conducted semistructured interviews, 1 hour in length, with 37 medical and public health professionals in the greater Pittsburgh area who played a decision-making role in vaccine allocation, whether from an administrative or direct care perspective. Investigators used preprepared questions to inquire about a person's initial and evolving awareness about the vaccine shortage and its institutional implications, and about the design, implementation, communication, and social acceptance of local vaccine rationing policy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] Over a 16-week period from January to May 2005, the authors conducted semistructured interviews, 1 hour in length, with 37 medical and public health professionals in the greater Pittsburgh area who played a decision-making role in vaccine allocation, whether from an administrative or direct care perspective. Investigators used preprepared questions to inquire about a person's initial and evolving awareness about the vaccine shortage and its institutional implications, and about the design, implementation, communication, and social acceptance of local vaccine rationing policy.…”
Section: Methodsmentioning
confidence: 99%
“…20,22 People's ability to call on prior relationships provides a high degree of flexibility and innovation with which to handle local contingencies. If, however, a group exists at the fringes of personal and professional networks, then they may have less opportunity to advocate for their needs or present aid to others in need.…”
Section: Informal Arrangements and Relationships Facilitated Providermentioning
confidence: 99%
“…An ethnographic study of how health care professionals accommodate the needs of stroke patients suggests that an individual's level of knowledge about how health and social care systems work (said to be a form of social capital) influences the quality of care they received [36]. Our study of younger stroke survivors found that for a minority cultural capital in the form of tacit knowledge of skills and knowledge shaped reported experiences of care and unmet need.…”
Section: Discussionmentioning
confidence: 79%
“…To identify the level of severity of violence that each participant suffered, it was inquired by experimentation for each item; when responding yes to at least one of them, the level of severity of each woman on the item with the highest score was considered. In this way there was no certainty of need but probability of need, accepting the problematic nature of the need promulgated from sociology, and contrary to the dichotomizing biomedical logic (19) . …”
Section: Measurement Of Need (N)mentioning
confidence: 99%